Optic nerve sheath diameter: a mean of detecting raised intracranial pressure in adult traumatic and non-traumatic patients - Mohd Ali, Mohd Raffiz (2015)
(ONSD) is emerging as a non-invasive technique to evaluate and predict raised intracranial pressure (ICP). It has been shown in previous literature that ONSD measurement has good correlation with surrogate findings of raised ICP such as clinical and radiological findings suggestive of raised ICP. Objectives: The objective of the study is to find a correlation between sonographic measurement of ONSD value with ICP value measured via the gold standard invasive intracranial ICP catheter, and to find the cut-off value of ONSD measurement in predicting raised ICP, along with its sensitivity and specificity value. Finally, we would also like to assess if this bedside non-invasive technique is more accurate in predicting raised ICP in traumatic or non-traumatic causes of raised ICP. Methods: A prospective observational study was performed using convenience sample of 41 adult neurosurgical patients treated in neurosurgical intensive care unit with invasive intracranial pressure monitoring placed in-situ as part of their clinical care. Portable SonoSite ultrasound machine with 7MHz linear probe were used to measure optic nerve sheath diameter using the standard technique. Simultaneous ICP readings were obtained directly from the invasive monitoring. Spearman rank correlation coefficient was used to assess the correlation between ONSD value and ICP value. High ICP was defined as ICP>20mmHg, and a receiver operator characteristic (ROC) curve was performed to find the ONSD cut-off point in predicting raised ICP, and to measure the sensitivity and specificity of both groups. Results: 75 ONSD measurements were performed on 41 patients. The non-parametric Spearman’s correlation test revealed a significant correlation at the 0.01 level between the ICP and ONSD value, with correlation coefficient of 0.820. The receiver operator characteristic (ROC) curve generated an area under the curve with the value of 0.964, and with standard error of 0.22. At 95% confidence interval, the lower boundary for this area under the curve is 0.921 and the upper boundary is 1.000. From the ROC curve, we found that the ONSD value of 5.205mm is 95.8% sensitive and 80.4% specific in detecting raised ICP. When similar ONSD value was analyzed; 5.47mm vs 5.48mm, the sensitivity and specificity of this value in predicting raised ICP is higher in the Traumatic group (94.4% sensitive and 95.2% specific) compared to Nontraumatic group (83.3% sensitive and 93.3% specific). Conclusions: ONSD value of 5.205 is sensitive and specific in detecting raised ICP. Bedside ultrasound measurement of ONSD is readily learned, and is reproducible and reliable in predicting raised ICP in both trauma and non-trauma group. This noninvasive technique can be a useful adjunct to the current invasive intracranial catheter monitoring, and has wide potential clinical applications in district hospitals, emergency departments and intensive care units.